2021
DOI: 10.1155/2021/5462633
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Effects of Centella asiatica on Skin Diseases: Evidence and Possible Mechanisms

Abstract: The medicinal herb Centella asiatica (L.) Urban known as gotu kola has been reported to exhibit a wide range of pharmacological activities. In particular, a significant body of scientific research exists on the therapeutic properties of preparations of C. asiatica or its triterpenes in the treatment of skin diseases. The present study is aimed to provide a comprehensive overview of the beneficial effects of C. asiatica on skin diseases. Peer-reviewed articles on the potent dermatological effects of C. asiatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 70 publications
(78 reference statements)
2
14
0
1
Order By: Relevance
“…The results of the current study also correspond with those of the wound healing effect of C. asiatica reported previously [ 29 ], that it promoted wound repair by stimulating fibroblast proliferation and collagen synthesis; thereby to enhance cell growth in burn wounds [ 30 ]. A hydrogen gel preparation of C. asiatica extract has been reported to result in accelerated wound healing in mice [ 31 ].…”
Section: Resultssupporting
confidence: 91%
“…The results of the current study also correspond with those of the wound healing effect of C. asiatica reported previously [ 29 ], that it promoted wound repair by stimulating fibroblast proliferation and collagen synthesis; thereby to enhance cell growth in burn wounds [ 30 ]. A hydrogen gel preparation of C. asiatica extract has been reported to result in accelerated wound healing in mice [ 31 ].…”
Section: Resultssupporting
confidence: 91%
“…Despite the reduced number of studies with focus on the inflammatory phase when compared to another phase of wound healing, the anti-inflammatory activity of CAE and Aa might be strongly evidenced in the inflammatory skin diseases models, such as psoriasis and atopic dermatitis [ 30 , 31 , 41 ]. Experimental studies performed in different animals models of wound healing, including phthalic anhydride (PA)-induced atopic dermatitis, excision, incision, burn and diabetic wounds models, have shown that the topical and oral administration of CAE reduces massive neutrophil recruitment accompanied by reducing release of TNF-α, IL-1β, IL-6, and IgE, and inhibition of the expression of iNOS, COX-2, NF-κB and lipoxygenase (LOX) activity in the site of skin injury [ 31 , 32 , 41 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Recently, Kukula et al [ 53 ] showed that asiatic acid treatment (100 mg/kg, p.o) suppressed the imiquimod-induced increase in serum levels of IL-17A and IL-23 in the imiquimod-induced psoriasis model [ 53 ].…”
Section: Centella Asiatica and Cutaneous Repair Processmentioning
confidence: 99%
“…The experimental and clinical findings have suggested that many of the beneficial effects on cutaneous repair process produced by C. asiatica are directly associated with their actions on the proliferative phase of the wound healing process, such as stimulation of fibronectin and collagen synthesis, maintenance of connective tissue and the strengthening of weakened veins [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. Asiatic acid has been reported to possess wound healing activity by increasing collagen formation and angiogenesis.…”
Section: Centella Asiatica and Cutaneous Repair Processmentioning
confidence: 99%
See 2 more Smart Citations